Evaluation of genotype resistance testing for salvage antiretroviral therapy at AIDS care centers from Ribeirão Preto, São Paulo, Brazil - Pires Neto,R.J. (2008)
The availability of HIV-1 genotype resistance testing (GRT) to clinicians has been insufficiently studied outside randomized clinical trials. The present study evaluated the outcome of salvage antiretroviral therapy (ART) recommended by an expert physician based on GRT in a non-clinical trial setting in Ribeirão Preto, Brazil. A prospective, open, nonrandomized study evaluating easy access to GRT at six Brazilian AIDS Clinics was carried out. This cooperative study analyzed the efficacy of treatment recommended to patients whose salvage ART was guided by GRT with that of treatment with ART based only on previous ART history. A total of 112 patients with ART failure were included in the study, and 77 of them were submitted to GRT. The median CD4 cell count and viral load for these 77 patients at baseline were (mean ± SD) 252.1 ± 157.4 cells/µL and 4.60 ± 0.5 log10 HIV RNA copies/mL, respectively. The access time, i.e., the time elapsed between ordering the GRT and receiving the result was, on average, 71.9 ± 37.3 days. The study results demonstrated that access to GRT followed by expert recommendations did not improve the time to persistent treatment failure when compared to conventional salvage ART. Access to GRT in this Brazilian community health care setting did not improve the long-term virologic outcomes of HIV-infected patients experiencing treatment failure. This result is probably related to the long time required to implement ART guided by GRT.